US-Trained Chinese (Returned) Scientific Diaspora, the Transformation of Modern China, and the Evolution of Sino-American Relations from the Mid-19th Century to the Present - Caixia Tan (Revue LISA)
This article deals with a small but significant fraction of the Chinese diasporas, namely the US-trained Chinese (returned) intellectual and scientific diaspora, which have been influential both in the transformation of modern China and in the shaping of US-China relations from the mid-19th century to the present. The approach of this paper is more historical than conceptual as we take a long-term perspective on the subject. At the nexus of their home country’s domestic and international affairs, scientific diasporas can be considered as a powerful social force. They exert influences both on homeland (foreign) policies and foreign policy decisions in the hostland. In the case of the US-trained Chinese (returned) scientific diaspora, they have been on the front line of successive battlefields of ideas concerning China’s development paths as well as its stance towards the United States. On the one hand, as facilitators of knowledge diffusion and technology transfer, and as implementers of imported “advanced” ideas, concepts, and technologies, they have played an important role in the (trans)formation of China’s modern educational, political, and technological systems. On the other hand, they have also been initiators and important actors in US-China transnational cooperation, especially in the field of science and technology. Our analysis will follow a chronological order. It will focus on two main historical periods: the pre-1979 era, or the legacy of the past, followed by the post-1979 era in which both the size and the impact of the scientific diaspora have been increasing since the establishment (in 1979) of the bilateral diplomatic relationship between the US and the People’s Republic of China (PRC).